The Effect of Differential and Traditional Trainings on Electromyographic Changes of Upper Torso Muscles in Performing and Learning Breaststroke Swimming - Nikravesh, Raha; Mousavi Sadati, Seyed Kazem; Bagherli, Jale; Aslan Khani , Mohammad Ali (Journal of Clinical Physiotherapy Research, 2022)
Introduction: Based on the principles of the self-organization system, making a change in the training composition can lead to more motor learning compared to doing repetitive training. The aim of this study was to investigate the Effect of differential and traditional trainings on electromyographic changes of upper torso muscles in performing and learning swimming breaststroke. Materials and Methods: In this quasi experimental study, 36 female swimmers aged 20 to 25 years old were randomly divided into three groups of control, traditional training, and differential training. Individuals of two groups were treated in two traditional and differential ways, and the control group continued their daily activities without any training. Before and after 12-sessions of trainings, the amount of activity in lower torso muscles, including pectorals major, latissimus dorsi, biceps, and triceps, were measured using electromyography respectively. Covariance multivariate analysis was used to compare the pattern of muscles activities and to evaluate the effect of training sessions on muscles activities. Results: Twelve sessions of differential training resulted in significant increases in the average of muscle activity RMS in four muscles compared to the control group. However, these changes were not statistically significant in the traditional training group compared to the control group for the latissimus dorsi muscle. Also, after 12 sessions of training, a significant increase was found in all muscles activities between the control group and the differential. However, this increase between the control and traditional groups was significant only in Latissimus dorsi and biceps. The significant increase between the traditional and differential groups was found in pectoralis major muscle. Conclusions: The findings of the present study indicated that the differential training are more effective than traditional training in learning breaststroke swimming, which can be due to more effective use of muscles during the training.